2012
DOI: 10.1590/s0100-736x2012000800010
|View full text |Cite
|
Sign up to set email alerts
|

Sheep abortion associated with Neospora caninum in Mato Grosso do Sul, Brazil

Abstract: Pesq. Vet. Bras. 32(8) Canids are the main hosts of Neospora caninum, but cattle, (sheep, goats and horses may serve as intermediary hosts. N. caninum infection of pregnant intermediary hosts may provoke abortion and neonatal infections. This study is the ϐirst to report lamb abortion associated with N. caninum in Mato Grosso do Sul. Epidemiological data were obtained from interviews with sheep producers. For microscopic examination, fragments of different organs removed from 4 sheep fetuses, aborted and necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
9
0
3
Order By: Relevance
“…A transmissão também pode ser vertical via transplacentária, que possui grande importância pois o animal clinicamente sadio se torna cronicamente infectado (Dubey & Acland 1992). A infecção possui grande importância econômica, principalmente devido às perdas reprodutivas, incluindo retornos ao cio, com intervalos regulares ou irregulares, abortos, nascimento de animais fracos e inviáveis, com sinais neurológicos, ou persistentemente infectados (Dubey & Lindsay 1996, Pinto et al 2012.…”
Section: Introductionunclassified
“…A transmissão também pode ser vertical via transplacentária, que possui grande importância pois o animal clinicamente sadio se torna cronicamente infectado (Dubey & Acland 1992). A infecção possui grande importância econômica, principalmente devido às perdas reprodutivas, incluindo retornos ao cio, com intervalos regulares ou irregulares, abortos, nascimento de animais fracos e inviáveis, com sinais neurológicos, ou persistentemente infectados (Dubey & Lindsay 1996, Pinto et al 2012.…”
Section: Introductionunclassified
“…In the state of Mato Grosso do Sul, Pinto et al (2012) confirmed vertical transmission of N. caninum in sheep fetuses and observed mild to moderate perivascular mononuclear infiltrate in heart and diffuse gliosis associated with non--suppurative mononuclear cells in brain. One of the brain samples evaluated by Pinto et al (2012) had cysts, which were confirmed as N. caninum cysts by IHC.…”
Section: Discussionmentioning
confidence: 66%
“…There are also reports of abortion in goats naturally infected by N. caninum in the United States (Barr et al 1992, Costa Rica (Dubey et al 1996), Italy (Eleni et al 2004), Spain (Moreno et al 2012) and Argentina (Unzaga et al 2014). In Brazil, N. caninum congenital infection in goats and sheep has been described in the South, Southeast and Midwest regions, with no descriptions in the other regions of the country (Corbellini et al 2001, Pinto et al 2012, Varaschin et al 2012, Mesquita et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Neospora caninum and Toxoplasma gondii are closely related cyst-forming apicomplexan parasites identified as important causes of reproductive failure in cattle [13,14]. Abortion cases attributed to N. caninum [12,21,35] and T. gondii [10,20,28,44] infection have been occasionally reported in sheep. These parasites have already been identified in 77% of 74 brain samples from aborted sheep fetuses [23].…”
Section: Introductionmentioning
confidence: 99%